Light internal curing aggregate as well as preparation method and application thereof
By preparing lightweight internal curing aggregates, using the porous structure of the ceram and the carbonation of the carbonate solution, the problems of heavy quality and uneven carbonation of the carbonated gelling materials are solved, and the lightweight and mechanical properties of concrete are improved.
Patent Information
- Application Number
- CN202411988518.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
The existing carbonated gelling materials have problems of heavier quality and uneven carbonation inside and outside, which affects their application in prefabricated buildings and other fields.
A light internal curing aggregate is prepared by immersing dried ceratops in a carbonate solution for impregnation treatment, and then coated with polyvinyl alcohol and calcium silicate to form a porous structure of light internal curing aggregate, thereby improving the carbonation degree and mechanical properties of the material.
The lightweight concrete is achieved, the concrete mass is reduced by more than 20%, and the carbonation degree and mechanical properties of the material are improved, solving the contradiction between lightweight and high strength of carbonated precast concrete.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new building materials, and specifically to a lightweight internal curing aggregate and a preparation method and application thereof. Background Art
[0002] Prefabricated buildings are buildings assembled on site using prefabricated parts and components. They have many advantages, such as good structural quality, high production efficiency, low energy and resource consumption, and reduced labor pressure. At present, the prefabricated components used in prefabricated concrete buildings are mainly produced in standardized factories by ordinary Portland cement concrete. Ordinary Portland cement mainly relies on the hydration reaction of hydratable calcium silicate minerals such as tricalcium silicate (C3S) and β-dicalcium silicate (β-C2S) to cement and harden. Due to the insufficient hydration rate at room temperature, steam curing is often used to accelerate hydration and hardening when producing prefabricated components, shorten the production cycle and improve the mold turnover efficiency, but it also causes a lot of energy consumption.
[0003] In the past, people focused on the hydration activity of calcium silicate minerals. Recent studies have shown that most types of calcium silicate minerals can rapidly undergo carbonation reactions with high concentrations of carbon dioxide (CO2) under wet conditions. Compared with hydration reactions, the carbonation hardening rate is faster, which has also led to the birth and development of new calcium silicate carbonate cementitious materials and their precast concrete components.
[0004] However, it is inevitable that carbonated concrete will face the same problem of self-weight as ordinary concrete, which not only increases the transportation cost of prefabricated components, but also poses challenges to its hoisting construction in high-rise buildings, limiting its application in fields such as prefabricated buildings. Replacing traditional coarse aggregates with lightweight aggregates can effectively achieve lightweight concrete, which can usually reduce the weight of concrete by more than 20%. In addition, since the gas is transmitted from the outside to the inside during the carbonation reaction, as the reaction proceeds, the pores will be gradually filled by the carbonation products, resulting in uneven carbonation inside and outside.
[0005] The Chinese patent "CN202010860721-A method for preparing a carbonation internal curing agent for cement-based materials by surface hydrophobic modification" uses molecular sieves as the raw material of the internal curing agent, performs surface hydrophobic modification or surface coating release control treatment, so that the molecular sieve has hydrophobic properties, and then adsorbs CO2 on it to introduce CO2 into the cement-based material. This patent uses molecular sieves as CO2 carriers for air entrainment. Although it can improve the carbonation degree and compressive strength of cement-based materials, molecular sieves have strong water absorption and need to be hydrophobic modified, which may affect the adsorption of CO2, and the cement-based materials are not lightweight.
[0006] Therefore, it is urgent to study a material that can reduce the quality of carbonated cementitious materials and improve the uneven carbonation inside and outside the material. Summary of the invention
[0007] In view of the problems and shortcomings in the prior art, the purpose of the present invention is to provide a lightweight internal curing aggregate and a preparation method and application thereof.
[0008] To achieve the purpose of the invention, the technical solution adopted by the present invention is as follows:
[0009] The first aspect of the present invention provides a method for preparing a lightweight internally cured aggregate, comprising the following steps:
[0010] S1, immersing the dried ceramsite in a curing agent, performing an immersion treatment under a vacuum environment, filtering after the immersion, and collecting the ceramsite; wherein the curing agent is a carbonate solution;
[0011] S2, immersing the ceramsite treated in step S1 into a coating solution, so that the coating solution is evenly covered on the surface of the ceramsite, filtering, and collecting the ceramsite;
[0012] S3, wrapping the powder material on the surface of the ceramsite treated in step S2, and drying, so as to obtain a lightweight internal curing aggregate.
[0013] According to the above preparation method, preferably, in step S1, the carbonate is sodium carbonate or ammonium bicarbonate; more preferably, the carbonate is ammonium bicarbonate.
[0014] According to the above preparation method, preferably, in step S1, the mass percentage concentration of the carbonate solution is 5% to 20%; more preferably, the mass percentage concentration of the carbonate solution is 5% to 15%; most preferably, the mass percentage concentration of the carbonate solution is 10%.
[0015] According to the above preparation method, preferably, in step S2, the coating layer solution is a polyvinyl alcohol solution.
[0016] According to the above preparation method, preferably, the mass percentage concentration of the polyvinyl alcohol solution is 0.5% to 5%; more preferably, the mass percentage concentration of the polyvinyl alcohol solution is 0.5% to 4%; most preferably, the mass percentage concentration of the polyvinyl alcohol solution is 2%.
[0017] According to the above preparation method, preferably, the molecular weight of the polyvinyl alcohol is between 24,000 and 98,000; more preferably, the polyvinyl alcohol is polyvinyl alcohol 2488 type.
[0018] According to the above preparation method, preferably, in step S3, the powder material is at least one of silicate minerals, alkaline earth metal oxides, and alkaline earth metal hydroxides. More preferably, the silicate mineral is at least one of calcium silicate minerals and magnesium silicate minerals; the calcium silicate mineral is at least one of monocalcium silicate, dicalcium silicate, and dicalcium trisilicate; the magnesium silicate mineral is at least one of olivine and serpentine; the alkaline earth metal oxide is at least one of calcium oxide and magnesium oxide; the alkaline earth metal hydroxide is at least one of calcium hydroxide and magnesium hydroxide. The selection of powder material for ceramsite coating is determined by the application scenario of lightweight internal curing aggregate. For example, when lightweight internal curing aggregate is used to prepare cementitious material, the powder material for ceramsite coating should be as consistent as possible with the raw material with the largest proportion in the cementitious material. The use of powder material to coat ceramsite can avoid adhesion between ceramsites, and also avoid ceramsite adsorbing other impurity materials.
[0019] According to the above preparation method, preferably, in step S1, the vacuum degree of the vacuum environment is 10Pa~30Pa, and the standing time is 2h~10h; more preferably, the vacuum degree of the vacuum environment is 10Pa~30Pa, and the immersion treatment time is 4h~8h; most preferably, the vacuum degree of the vacuum environment is 20Pa, and the immersion treatment time is 6h.
[0020] According to the above preparation method, preferably, the particle size of the ceramsite is 0.60 mm to 9.50 mm; more preferably, the particle size of the ceramsite is 1.18 mm to 4.75 mm; most preferably, the particle size of the ceramsite is 2.36 mm.
[0021] According to the above preparation method, preferably, in step S3, the mass ratio of the powder material to the ceramsite is 1:(1-3); more preferably, the mass ratio of the powder material to the ceramsite is 1:2.
[0022] According to the above preparation method, preferably, in step S2, the ceramsite treated in step S1 needs to be stirred after being immersed in the coating solution, and the stirring rate is 10 r / min to 50 r / min, and the stirring time is 1 min to 5 min.
[0023] According to the above preparation method, preferably, in step S1, the ceramsite is shale ceramsite.
[0024] According to the above preparation method, preferably, in step S1, the drying temperature is 20°C to 80°C, and the drying time is 12h to 24h; more preferably, the drying temperature is 80°C, and the drying time is 24h.
[0025] According to the above preparation method, preferably, in step S3, the drying is natural air drying, and the natural air drying time is 6 hours to 12 hours.
[0026] The second aspect of the present invention provides a lightweight internally cured aggregate product prepared using the preparation method described in the first aspect.
[0027] The third aspect of the present invention provides the use of the lightweight internal curing aggregate product described in the second aspect in cementitious materials or concrete.
[0028] According to the above application, preferably, the cementitious material is a carbonated cementitious material, and the concrete includes a precast concrete component.
[0029] A fourth aspect of the present invention provides a carbonated cementitious material, wherein the carbonated cementitious material comprises the lightweight internal curing aggregate product described in the second aspect.
[0030] According to the above-mentioned carbonated cementitious material, preferably, it is composed of the following raw materials in parts by weight: 85 to 115 parts of cement, 10 to 50 parts of lightweight internal curing aggregate, and 45 to 70 parts of water.
[0031] According to the above-mentioned carbonated cementitious material, preferably, the cement is formed by mixing silicate cement and aluminate cement in a mass ratio of (16-19):(1-4); more preferably, the cement is formed by mixing silicate cement and aluminate cement in a mass ratio of 17:3; further, the silicate cement is preferably calcium silicate cement, and the aluminate cement is preferably calcium aluminate cement; further, the calcium silicate cement is at least one of monocalcium silicate cement, dicalcium silicate cement, and dicalcium trisilicate cement.
[0032] The fifth aspect of the present invention provides a method for preparing the above-mentioned cementitious material, and the preparation method is: the preparation method of the cementitious material is: adding cement and water into a mixer, stirring and mixing evenly, and then adding aggregate and stirring and mixing to obtain the cementitious material.
[0033] Compared with the prior art, the present invention has the following positive and beneficial effects:
[0034] (1) The present invention first immerses the dried ceramsite in a carbonate solution as a curing agent, so that the ceramsite fully absorbs the carbonate solution, and then sequentially coats the surface of the ceramsite with polyvinyl alcohol and calcium silicate to obtain a lightweight internal curing aggregate. After the lightweight internal curing aggregate is introduced into the mortar, its curing mechanism (such as Figure 1As shown in the figure, the mortar is first subjected to conventional carbonation curing. During the carbonation curing process, the silicate cement in the mortar is carbonated to generate CaCO3(I), and during the carbonation process, the coating layer solvent on the surface of the ceramsite begins to dissolve under the action of water. However, the carbonation rate of the cement in the mortar is much higher than the dissolution rate of the coating layer solvent. Therefore, the coating layer solvent on the surface of the ceramsite can hinder the premature release of the curing agent inside the ceramsite during the cement carbonation process. This stage is mainly based on the carbonation curing of the cement in the mortar. When the carbonation curing of the cement in the mortar is basically completed (the carbonation curing rate is very fast, basically completed within one day), the coating layer solvent on the surface of the ceramsite is The coating layer solvent is basically dissolved. At this time, the test block prepared by mortar is cured in a natural environment. During the natural curing process, the curing agent wrapped inside the expanded clay is gradually released from the expanded clay. The bicarbonate ions or carbonate ions in the released curing agent further react with the calcium ions in the mortar system to generate CaCO3(II) precipitates. The newly formed CaCO3(II) strengthens the structure of the CaCO3(I) composition and reduces the pores, thereby increasing the degree of carbonation inside the material and improving the overall strength of the material, thereby improving the mechanical properties of the material and solving the contradiction between light weight and high strength of carbonated precast concrete.
[0035] (2) The present invention mixes the ceramsite with the curing agent and then performs an immersion treatment in a vacuum environment. The vacuum environment is conducive to the curing agent entering the interior of the ceramsite, so that the ceramsite fully absorbs the curing agent, thereby obtaining adsorption-saturated ceramsite.
[0036] (3) The lightweight internal curing aggregate of the present invention can replace traditional aggregates to effectively achieve lightweight concrete. Compared with concrete with traditional aggregates, the weight of concrete can usually be reduced by more than 20%. At the same time, since the lightweight internal curing aggregate has a porous structure, the thermal insulation performance of concrete can be significantly improved.
[0037] (4) The raw materials of the lightweight internal curing aggregate prepared by the present invention are easy to obtain, low in cost, simple in preparation method, and easy to use. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The curing mechanism of the lightweight internally cured aggregate of the present invention;
[0039] Figure 2 Backscattered images of cementitious material P3 specimen after extended curing for 3 days: (a) close to the aggregate area; (b) far from the aggregate area;
[0040] Figure 3 Backscattered images of cementitious material P8 sample after extended curing for 3 days: (a) close to the aggregate area; (b) far from the aggregate area. DETAILED DESCRIPTION
[0041] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0042] The following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0043] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. When the terms "comprise" and / or "include" are used in this specification, it indicates that there are features, steps, operations, parts and / or combinations thereof.
[0044] The experimental methods in the following examples without specifying specific conditions all adopt conventional techniques in the art or follow the conditions recommended by the manufacturers; the reagents or instruments used without specifying the manufacturers are all conventional products that can be obtained commercially.
[0045] Example 1: Discussion on particle size of ceramsite
[0046] In order to study the effect of ceramsite particle size on the performance of lightweight internal curing aggregate, the present invention carried out Examples 1-1 to 1-5 and Comparative Example 1. The specific contents of Examples 1-1 to 1-5 are as follows:
[0047] Example 1-1:
[0048] A method for preparing a lightweight internal curing aggregate, the specific steps are as follows:
[0049] S1. Dry the shale ceramsite at 80° C. for 24 hours, immerse the dried shale ceramsite with a particle size of 0.06 mm in a curing agent, mix well and place in a vacuum environment for immersion treatment, filter after immersion to remove excess curing agent, and collect the ceramsite; wherein the curing agent is an ammonium bicarbonate solution, and the mass percentage concentration of the ammonium bicarbonate solution is 10%; the vacuum degree of the vacuum environment is 20 Pa, and the immersion treatment time is 6 hours.
[0050] S2, immersing the ceramsite treated in step S1 into a coating solution, stirring at 30 r / min for 3 min to make the coating solution evenly cover the surface of the ceramsite, filtering, and collecting the ceramsite; wherein the coating solution is a polyvinyl alcohol solution, the mass percentage concentration of the polyvinyl alcohol solution is 2%, and the molecular weight of the polyvinyl alcohol is between 24000 and 98000 (preferably, the polyvinyl alcohol is polyvinyl alcohol 2488 type).
[0051] S3, sprinkling powder material on the surface of the ceramsite treated in step S2, so that the powder material is wrapped on the surface of the ceramsite, and then naturally air-drying the ceramsite to obtain a lightweight internal curing aggregate; wherein the powder material is dicalcium silicate powder, and the mass ratio of dicalcium silicate powder to ceramsite is 1:2.
[0052] The contents of Examples 1-2 to 1-5 are substantially the same as those of Example 1, except that in step S1, the particle sizes of the dried shale ceramsite are different. The particle sizes of the dried shale ceramsite in Examples 1-2 to 1-5 are 1.18 mm, 2.36 mm, 4.75 mm, and 9.50 mm, respectively.
[0053] In order to test the performance of the lightweight internally cured aggregate prepared in Example 1-1 to Example 1-5, the lightweight internally cured aggregate prepared in Example 1-1 to Example 1-5 was used to prepare cementitious materials, and the obtained cementitious materials were respectively recorded as cementitious material P1, cementitious material P2, cementitious material P3, cementitious material P4, and cementitious material P5. At the same time, for comparison, standard sand was used as aggregate to prepare cementitious material (the prepared cementitious material was recorded as P6), and the performance of cementitious materials P1 to P6 was tested.
[0054] The formula of the cementitious material is as follows: the cementitious material is made of the following raw materials in parts by weight: 85 parts of dicalcium silicate cement, 15 parts of calcium aluminate cement, 45 parts of water, and 40 parts of aggregate. The preparation method of the cementitious material is as follows: adding calcium silicate cement and calcium aluminate cement into a mortar mixer and dry mixing for 60 seconds, then adding water and stirring for 120 seconds, and then adding aggregate and stirring for another 60 seconds to obtain the cementitious material.
[0055] The testing method of the performance of cementitious materials is as follows: pour the cementitious materials into a 40mm×40mm×40mm mold, then cover with plastic wrap to prepare the sample; put the sample into a curing box, and cure it for 24 hours at a temperature of 50°C and a relative humidity of more than 85% to minimize the evaporation of sample water; after demoulding, put the sample into a blast drying box at a drying temperature of 80°C for pre-drying for 1 hour; after drying, take out the sample and cool it to room temperature, then wrap the sample with plastic wrap and let it stand at room temperature for 24 hours to make the moisture distribution inside the dried sample uniform; then put these samples into a carbonation device, inject 99.9% pure CO2 at a constant pressure of 0.2MPa, and carbonate for 12 hours; after the carbonation curing is completed, test the compressive strength, volume density, apparent porosity, and carbonation degree of the sample. Among them, the compressive strength is the compressive strength of the sample after the carbonation curing is completed and the curing is continued for three days. The bulk density is determined according to the national standard "Test method for bulk density of refractory particles" GB / T 2999-2016. The apparent porosity is determined according to the national standard "Test method for bulk density, apparent porosity and true porosity of dense shaped refractory products" GB / T2997-2015. The carbonation degree is the ratio of the CO2 mass actually absorbed by the sample after carbonation to the maximum CO2 mass that it can theoretically absorb; the carbonation degree is calculated by measuring the mass loss of the sample at 300-800℃.
[0056] The performance test results of cementitious materials P1 to P6 prepared using the aggregates prepared in Examples 1-1 to 1-5 and Comparative Example 1 as raw materials are shown in Table 1.
[0057] Table 1 Effect of ceramsite particle size on cementitious material properties
[0058]
[0059] As can be seen from Table 1, the bulk density of cementitious materials P1 to P5 is lower than that of cementitious materials prepared with standard sand as aggregate, indicating that the mass of cementitious materials can be reduced when the lightweight internal curing aggregate prepared by Examples 1-1 to 1-5 of the present invention is used to prepare cementitious materials. In addition, the compressive strength of cementitious materials P1 to P5 is significantly higher than that of cementitious materials prepared with standard sand as aggregate, indicating that the lightweight internal curing aggregate prepared by the present invention improves the overall strength of cementitious materials through the effect of internal curing. Moreover, with the increase of ceramsite particle size, the compressive strength, bulk density and carbonation degree of the prepared cementitious materials gradually increase. When the ceramsite particle size is 2.36 mm, the bulk density, compressive strength and carbonation degree of the cementitious materials all reach the maximum; when the ceramsite particle size is further increased, the compressive strength of the prepared cementitious materials shows a downward trend. This is because when the ceramsite particle size is too large, its volume accounts for too large a proportion of the entire sample, thereby reducing the compressive strength of the sample. Therefore, the particle size of the ceramsite is preferably 1.18 to 4.75 mm, more preferably 2.36 mm.
[0060] Example 2: Discussion on types of internal curing agents
[0061] In order to study the effect of the type of internal curing agent on the performance of lightweight internal curing aggregate, the present invention carried out Example 2-1 to Example 2-2. The specific contents of Example 2-1 to Example 2-2 are as follows:
[0062] Example 2-1:
[0063] A method for preparing a lightweight internal curing aggregate, the specific steps are as follows:
[0064] S1. Dry the shale ceramsite at 80° C. for 24 h, immerse the dried shale ceramsite with a particle size of 2.36 mm in a curing agent, mix well and place in a vacuum environment for immersion treatment, filter after immersion to remove excess curing agent, and collect the ceramsite; wherein the curing agent is a sodium bicarbonate solution, and the mass percentage concentration of the sodium bicarbonate solution is 10%; the vacuum degree of the vacuum environment is 20 Pa, and the immersion treatment time is 6 h.
[0065] S2, immersing the ceramsite treated in step S1 into a coating solution, stirring at 30 r / min for 3 min to make the coating solution evenly cover the surface of the ceramsite, filtering, and collecting the ceramsite; wherein the coating solution is a polyvinyl alcohol solution, the mass percentage concentration of the polyvinyl alcohol solution is 2%, and the molecular weight of the polyvinyl alcohol is between 24000 and 98000 (preferably, the polyvinyl alcohol is polyvinyl alcohol 2488 type).
[0066] S3, sprinkling powder material on the surface of the ceramsite treated in step S2, so that the powder material is wrapped on the surface of the ceramsite, and then naturally air-drying the ceramsite to obtain a lightweight internal curing aggregate; wherein the powder material is dicalcium silicate powder, and the mass ratio of the dicalcium silicate powder to the ceramsite is 1:2.
[0067] The content of Example 2-2 is basically the same as that of Example 2-1, except that in step S1, the curing agent is water.
[0068] In order to test the performance of the aggregates prepared in Example 2-1 to Example 2-2, the aggregates prepared in Example 2-1 to Example 2-2 were used to prepare cementitious materials, and the obtained cementitious materials were respectively recorded as cementitious material P7 and cementitious material P8. The performance of cementitious materials P7 and P8 was tested and compared with cementitious materials P3 and P6. The results are shown in Table 2.
[0069] The formula and preparation method of the cementitious material are the same as those in Example 1, only the aggregate is replaced accordingly, which will not be described in detail. The method for testing the performance of the cementitious material is the same as that in Example 1.
[0070] Table 2 Effect of curing agent types on the performance of cementitious materials
[0071]
[0072] As shown in Table 2, there is no significant difference in the bulk density, compressive strength and carbonation degree of the samples prepared from cementitious materials P7 and P8, and the compressive strength and carbonation degree of cementitious materials P7 and P8 are significantly lower than that of cementitious material P3. This shows that the use of water and sodium bicarbonate as curing agents does not play an internal curing role; the use of ammonium bicarbonate as an internal curing agent can greatly improve the compressive strength and carbonation degree of the cementitious material.
[0073] Among them, the backscattered images of the cementitious materials P3 and P8 samples after carbonation curing were extended for three days as shown in the following figure. Figure 2 and Figure 3 As shown. Figure 2 , Figure 3 As shown in the figure, when ammonium bicarbonate is used as an internal curing agent, the prepared cementitious material has fewer pores in the area close to the internal curing aggregate and is more dense. Therefore, ammonium bicarbonate is the most suitable curing agent.
[0074] Example 3: Discussion on the concentration of internal curing agent
[0075] In order to study the effect of the concentration of the internal curing agent on the performance of lightweight internal curing aggregate, the present invention carried out Examples 3-1 to 3-3. The specific contents of Examples 3-1 to 3-3 are as follows:
[0076] Example 3-1:
[0077] A method for preparing a lightweight internal curing aggregate, the specific steps are as follows:
[0078] S1. Dry the shale ceramsite at 80° C. for 24 h, immerse the dried shale ceramsite with a particle size of 2.36 mm in a curing agent, mix well and place in a vacuum environment for immersion treatment, filter after immersion to remove excess curing agent, and collect the ceramsite; wherein the curing agent is an ammonium bicarbonate solution, and the mass percentage concentration of the ammonium bicarbonate solution is 5%; the vacuum degree of the vacuum environment is 20 Pa, and the immersion treatment time is 6 h.
[0079] S2, immersing the ceramsite treated in step S1 into a coating solution, stirring at 30 r / min for 3 min to make the coating solution evenly cover the surface of the ceramsite, filtering, and collecting the ceramsite; wherein the coating solution is a polyvinyl alcohol solution, the mass percentage concentration of the polyvinyl alcohol solution is 2%, and the molecular weight of the polyvinyl alcohol is between 24000 and 98000 (preferably, the polyvinyl alcohol is polyvinyl alcohol 2488 type).
[0080] S3, sprinkling powder material on the surface of the ceramsite treated in step S2, so that the powder material is wrapped on the surface of the ceramsite, and then naturally air-drying the ceramsite to obtain a lightweight internal curing aggregate; wherein the powder material is dicalcium silicate powder, and the mass ratio of the dicalcium silicate powder to the ceramsite is 1:2.
[0081] The contents of Example 3-2 and Example 3-3 are basically the same as Example 3-1, except that in step S1, the mass percentage concentration of the ammonium bicarbonate solution is different. The mass percentage concentration of the ammonium bicarbonate solution in Example 3-2 and Example 3-3 is 15% and 20% respectively.
[0082] In order to test the performance of the aggregates prepared in Examples 3-1 to 3-3, the aggregates prepared in Examples 3-1 to 3-3 were used to prepare cementitious materials, and the obtained cementitious materials were respectively recorded as cementitious material P9, cementitious material P10, and cementitious material P11. The performance of cementitious materials P9 to P11 was tested and compared with cementitious materials P3 and P8. The results are shown in Table 3.
[0083] The formula and preparation method of the cementitious material are the same as those in Example 1, and only the aggregate is replaced accordingly. The method for testing the performance of the cementitious material is the same as that in Example 1, and will not be repeated here.
[0084] Table 3 Effect of curing agent concentration on cementitious material performance
[0085]
[0086] It can be seen from Table 3 that with the increase of the concentration of ammonium bicarbonate solution, the volume density of the prepared cementitious material gradually increases and tends to be stable; moreover, with the increase of the concentration of ammonium bicarbonate solution, the compressive strength and carbonation degree of the prepared cementitious material gradually increase. When the concentration of ammonium bicarbonate is 10%, the compressive strength and carbonation degree of the prepared cementitious material are the highest. When the concentration of ammonium bicarbonate solution is further increased, the compressive strength and carbonation degree of the prepared cementitious material decrease slightly. This is because with the increase of the concentration of the internal curing agent, more unreacted calcium silicate undergoes carbonation reaction, but when the concentration of the internal curing agent is too high, the dissolved HCO 3- and CO3 2- With Ca 2+ The rapid reaction generates calcium carbonate precipitation, which covers the surface of the calcium silicate mineral and hinders further reaction. Therefore, the concentration of the curing agent ammonium bicarbonate solution is preferably 5% to 20%, more preferably 10%.
[0087] Example 4: Study on the immersion treatment time
[0088] In order to study the effect of the impregnation treatment time on the performance of lightweight internally cured aggregate, the present invention carried out Examples 4-1 to 4-4. The specific contents of Examples 4-1 to 4-4 are as follows:
[0089] Example 4-1:
[0090] A method for preparing a lightweight internal curing aggregate, the specific steps are as follows:
[0091] S1. Dry the shale ceramsite at 80° C. for 24 h, immerse the dried shale ceramsite with a particle size of 2.36 mm in a curing agent, mix well and place in a vacuum environment for immersion treatment, filter after immersion to remove excess curing agent, and collect the ceramsite; wherein the curing agent is an ammonium bicarbonate solution, and the mass percentage concentration of the ammonium bicarbonate solution is 10%; the vacuum degree of the vacuum environment is 20 Pa, and the immersion treatment time is 2 h.
[0092] S2, immersing the ceramsite treated in step S1 into a coating solution, stirring at 30 r / min for 3 min to make the coating solution evenly cover the surface of the ceramsite, filtering, and collecting the ceramsite; wherein the coating solution is a polyvinyl alcohol solution, the mass percentage concentration of the polyvinyl alcohol solution is 2%, and the molecular weight of the polyvinyl alcohol is between 24000 and 98000 (preferably, the polyvinyl alcohol is polyvinyl alcohol 2488 type).
[0093] S3, sprinkling powder material on the surface of the ceramsite treated in step S2, so that the powder material is wrapped on the surface of the ceramsite, and then naturally air-drying the ceramsite to obtain a lightweight internal curing aggregate; wherein the powder material is dicalcium silicate powder, and the mass ratio of the dicalcium silicate powder to the ceramsite is 1:2.
[0094] The contents of Examples 4-2 to 4-4 are basically the same as those of Example 4-1, except that the immersion treatment time in step S1 is different. The immersion treatment in Examples 4-2 to 4-4 is 4h, 8h, and 10h, respectively.
[0095] In order to test the performance of the aggregates prepared in Examples 4-1 to 4-4, the aggregates prepared in Examples 4-1 to 4-4 were used to prepare cementitious materials, and the obtained cementitious materials were respectively recorded as cementitious material P12, cementitious material P13, cementitious material P14, and cementitious material P15. The performance of cementitious materials P12 to P15 was tested and compared with cementitious material P3. The results are shown in Table 4.
[0096] The formula and preparation method of the cementitious material are the same as those in Example 1, and only the aggregate is replaced accordingly. The method for testing the performance of the cementitious material is the same as that in Example 1, and will not be repeated here.
[0097] Table 4 Effect of immersion time on the properties of cementitious materials
[0098]
[0099] It can be seen from Table 4 that with the increase of the impregnation treatment time, the volume density, compressive strength and carbonation degree of the prepared cementitious material gradually increase; this is because the longer the impregnation time in the vacuum environment, the closer the dosage of the curing agent absorbed by the ceramsite is to saturation, so that more curing agent can be released during the curing process in the mortar. When the impregnation treatment time reaches 6h, the volume density, compressive strength and carbonation degree of the prepared cementitious material do not change significantly and tend to be stable when the impregnation time is further increased. This is because the absorption of the curing agent by the ceramsite during the impregnation process is basically close to saturation. Therefore, the impregnation treatment time is preferably 4h to 10h, and more preferably 6h.
[0100] Example 5: Discussion on the concentration of coating solution
[0101] In order to study the effect of coating solution concentration on the performance of lightweight internally cured aggregate, the present invention carried out Examples 5-1 to 5-6. The specific contents of Examples 5-1 to 5-6 are as follows:
[0102] Example 5-1:
[0103] A method for preparing a lightweight internal curing aggregate, the specific steps are as follows:
[0104] S1. Dry the shale ceramsite at 80° C. for 24 hours, immerse the dried shale ceramsite with a particle size of 2.36 mm in a curing agent, mix well and place in a vacuum environment for immersion treatment, filter after immersion to remove excess curing agent, and collect the ceramsite; wherein the curing agent is an ammonium bicarbonate solution, and the mass percentage concentration of the ammonium bicarbonate solution is 10%; the vacuum degree of the vacuum environment is 20 Pa, and the immersion treatment time is 6 hours.
[0105] S2, immersing the ceramsite treated in step S1 into a coating solution, stirring at 30 r / min for 3 min to make the coating solution evenly cover the surface of the ceramsite, filtering, and collecting the ceramsite; wherein the coating solution is a polyvinyl alcohol solution, the mass percentage concentration of the polyvinyl alcohol solution is 0.5%, and the molecular weight of the polyvinyl alcohol is between 24000 and 98000 (preferably, the polyvinyl alcohol is polyvinyl alcohol 2488 type).
[0106] S3, sprinkling powder material on the surface of the ceramsite treated in step S2, so that the powder material is wrapped on the surface of the ceramsite, and then naturally air-drying the ceramsite to obtain a lightweight internal curing aggregate; wherein the powder material is dicalcium silicate powder, and the mass ratio of the dicalcium silicate powder to the ceramsite is 1:2.
[0107] The contents of Examples 5-2 to 5-6 are basically the same as those of Example 5-1, except that: in step S2, the mass percentage concentration of the polyvinyl alcohol solution is different. The mass percentage concentration of the polyvinyl alcohol solution in Examples 5-2 to 5-6 is 1%, 3%, 4%, 5%, and 0%, respectively. The mass percentage concentration of the polyvinyl alcohol solution in Example 5-6 is 0%, which means that the ceramsite treated in step S1 is not coated with the polyvinyl alcohol solution, that is, the powder material is directly sprinkled on the surface of the ceramsite treated in step S1, so that the powder material is wrapped on the surface of the ceramsite, and then the ceramsite is naturally air-dried to obtain a lightweight internal curing aggregate.
[0108] In order to test the performance of the aggregates prepared in Examples 5-1 to 5-6, the aggregates prepared in Examples 5-1 to 5-6 were used to prepare cementitious materials, and the obtained cementitious materials were respectively recorded as cementitious material P16, cementitious material P17, cementitious material P18, cementitious material P19, cementitious material P20, and cementitious material P21. The performance of cementitious materials P16 to P21 was tested and compared with cementitious material P3. The results are shown in Table 5.
[0109] The formula and preparation method of the cementitious material are the same as those in Example 1, and only the aggregate is replaced accordingly. The method for testing the performance of the cementitious material is the same as that in Example 1, and will not be repeated here.
[0110] Table 5 Effect of coating solution concentration on the properties of cementitious materials
[0111]
[0112] It can be seen from Table 5 that with the increase of polyvinyl alcohol concentration, the volume density, compressive strength and carbonation degree of the prepared cementitious material show a trend of first increasing and then decreasing. This is because as the concentration of polyvinyl alcohol solution increases, the resistance of aggregate to release the internal curing agent becomes greater. After the coating of polyvinyl alcohol at a lower concentration, the coating layer formed on the surface of the ceramsite can prevent the curing agent inside the ceramsite from being released prematurely during the preparation of mortar mixing, thereby preventing the impact on the external carbonation. However, when the concentration of polyvinyl alcohol is too high, a dense coating layer is formed on the surface of the ceramsite after coating, which makes it difficult to release the curing agent inside the ceramsite, thereby affecting the effect of internal curing. Therefore, the concentration of polyvinyl alcohol is preferably 0.5% to 4%, and more preferably 2%.
[0113] Example 6: Discussion on the amount of lightweight internal curing aggregate in cementitious materials
[0114] In order to study the effect of the amount of lightweight internal curing aggregate in the cementitious material on the performance of the prepared cementitious material, the present invention carried out Examples 6-1 to 6-4. The specific contents of Examples 6-1 to 6-4 are as follows:
[0115] Example 6-1:
[0116] A cementitious material is prepared from the following raw materials in parts by weight: 85 parts of dicalcium silicate cement, 15 parts of calcium aluminate cement, 45 parts of water, and 10 parts of lightweight internal curing aggregate prepared in Example 1-3.
[0117] The preparation method of the above-mentioned cementitious material is: add calcium silicate cement and calcium aluminate cement into a mortar mixer and dry mix for 60 seconds, then add water and stir for 120 seconds, then add aggregate and stir for another 60 seconds to obtain the cementitious material.
[0118] The contents of Examples 6-2 to 6-4 are basically the same as those of Example 6-1, except that the amount of lightweight internal curing aggregate in the cementitious material formula is different. The amount of lightweight internal curing aggregate in the cementitious material formula in Examples 7-2 to 7-4 is 20 parts, 30 parts, and 50 parts, respectively.
[0119] The gelling materials prepared in Examples 6-1 to 6-4 were respectively recorded as gelling material P22, gelling material P23, gelling material P24, and gelling material P25. The properties of gelling materials P22 to P25 were compared with those of gelling materials P3 and P6. The results are shown in Table 6.
[0120] The formula and preparation method of the cementitious material are the same as those in Example 1, and the method for detecting the performance of the cementitious material is the same as that in Example 1, which will not be described in detail here.
[0121] Table 6 Effect of lightweight internal curing aggregate dosage on cementitious material performance
[0122]
[0123] It can be seen from Table 6 that with the increase in the amount of internal curing aggregate added, the compressive strength and bulk density of the cementitious material first increase and then decrease, and the degree of carbonation gradually increases and then tends to stabilize. Because adding an appropriate amount of internal curing aggregate can effectively improve the internal carbonation degree of the mortar without affecting the overall compressive strength of the mortar, thereby improving the overall compressive strength of the mortar. However, if the amount of aggregate added is too large, the proportion of ceramsite in the mortar is too high, the proportion of calcium silicate is relatively small, and it also affects the external carbonation, thereby reducing the compressive strength and bulk density of the mortar. Therefore, the amount of lightweight internal curing aggregate added is preferably 20 to 40 parts, and more preferably 40 parts.
[0124] Embodiment 8:
[0125] The content of Example 8 is basically the same as that of Examples 1-3, except that in step S3, the powder material is monocalcium silicate.
[0126] Embodiment 9:
[0127] The content of Example 9 is substantially the same as that of Examples 1-3, except that in step S3, the powder material is dicalcium trisilicate.
[0128] Embodiment 10:
[0129] The content of Example 10 is substantially the same as that of Examples 1-3, except that in step S3, the powder material is olivine powder.
[0130] Embodiment 11:
[0131] The content of Example 11 is basically the same as that of Examples 1-3, except that in step S3, the powder material is calcium oxide.
[0132] Embodiment 12:
[0133] The content of Example 12 is basically the same as that of Examples 1-3, except that in step S3, the powder material is magnesium oxide.
[0134] Embodiment 13:
[0135] The content of Example 13 is basically the same as that of Examples 1-3, except that in step S3, the powder material is calcium hydroxide.
[0136] Embodiment 14:
[0137] The content of Example 14 is basically the same as that of Examples 1-3, except that in step S3, the powder material is magnesium hydroxide.
[0138] Embodiment 15:
[0139] The content of Example 15 is basically the same as that of Examples 1-3, except that in step S3, the powder material is serpentine.
[0140] Embodiment 16:
[0141] A cementitious material is prepared from the following raw materials in parts by weight: 80 parts of monocalcium silicate cement, 20 parts of calcium aluminate cement, 45 parts of water, and 40 parts of lightweight internal curing aggregate prepared in Example 8. The preparation method of the cementitious material is the same as that of Example 6-1.
[0142] Embodiment 17:
[0143] A cementitious material is prepared from the following raw materials in parts by weight: 85 parts of dicalcium trisilicate cement, 15 parts of calcium aluminate cement, 45 parts of water, and 40 parts of the lightweight internal curing aggregate prepared in Example 9. The preparation method of the cementitious material is the same as that of Example 6-1.
[0144] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention, and are not intended to limit the present invention in other forms. Any technician familiar with the profession may use the above technical content as inspiration to make changes or modifications. This is an equivalent embodiment of equivalent changes. However, any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the technical concept of the present invention still fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a lightweight internal curing aggregate, characterized in that: The following steps are involved: S1, immersing the dried ceramsite in a curing agent, performing an immersion treatment under a vacuum environment, filtering after the immersion, and collecting the ceramsite; wherein the curing agent is a carbonate solution; S2, immersing the ceramsite treated in step S1 into a coating solution, so that the coating solution is evenly covered on the surface of the ceramsite, filtering, and collecting the ceramsite; S3, wrapping the powder material on the surface of the ceramsite treated in step S2, and drying, so as to obtain a lightweight internal curing aggregate.
2. The preparation method according to claim 1, characterized in that: In step S1, the carbonate is sodium carbonate or ammonium bicarbonate.
3. The preparation method according to claim 2, characterized in that: In step S1, the mass percentage concentration of the carbonate solution is 5% to 20%.
4. The preparation method according to any one of claims 1 to 3, characterized in that: In step S2, the coating layer solution is a polyvinyl alcohol solution, and the mass percentage concentration of the polyvinyl alcohol solution is 0.5% to 5%; in step S3, the powder material is at least one of silicate minerals, alkaline earth metal oxides, and alkaline earth metal hydroxides.
5. The preparation method according to claim 4, characterized in that: In step S1, the vacuum degree of the vacuum environment is 10Pa~30Pa, the immersion treatment time is 2h~10h; the particle size of the ceramsite is 0.60mm~9.50 mm; the molecular weight of the polyvinyl alcohol is 24000~98000; the silicate mineral is at least one of calcium silicate mineral and magnesium silicate mineral; the calcium silicate mineral is at least one of monocalcium silicate, dicalcium silicate, and dicalcium trisilicate; the magnesium silicate mineral is at least one of olivine and serpentine; the alkaline earth metal oxide is at least one of calcium oxide and magnesium oxide; and the alkaline earth metal hydroxide is at least one of calcium hydroxide and magnesium hydroxide.
6. A lightweight internally cured aggregate product prepared by the preparation method according to any one of claims 1 to 5.
7. Use of the lightweight internal curing aggregate product according to claim 6 in cementitious materials or concrete.
8. A carbonated gelling material, characterized in that: The lightweight internally cured aggregate product comprises the lightweight internally cured aggregate product according to claim 6.
9. The carbonated gelling material according to claim 8, characterized in that: The invention is composed of the following raw materials in parts by weight: 85 to 115 parts of cement, 10 to 50 parts of lightweight internal curing aggregate and 45 to 70 parts of water.
10. The carbonated gelling material according to claim 9, characterized in that: The cement is prepared by mixing silicate cement and aluminate cement in a mass ratio of (16-19):(1-4).
Citation Information
Patent Citations
A method for preparing a carbonation internal curing agent for cement-based materials by surface hydrophobic modification
CN111943547B